Influence of hydroperoxide epoxidation reaction conditions of octen-1 on the process of Mo2B activation and on the selectivity of epoxide formation - Комаренська, З. М.; Никипанчук, М. В.; Макота, О. І.; Олійник, Л. П.; Komarenska, Z. M.; Nykypanchuk, M. V.; Makota, O. I.; Oliynyk, L. P. (Видавництво Львівської політехніки, 2020)
Проведено дослідження процесу активування молібденборидного каталізатора в реакції епоксидування октену-1 трет-бутилгідропероксидом і вплив на згаданий процес початкової концентрації октену-1, трет-бутилгідропероксиду і кількості каталізатора в реакційній суміші, а також продуктів реакції (трет-бутилового спирту і епоксиду). Показано, що в часі на поверхні Мо2В утворюється нова аморфна фаза, яка власне каталізує реакцію епоксидування октену-1 третбутилгідропероксидом. Утворення цієї фази є причиною прискорення швидкості витрати гідропероксиду і селективності утворення епоксиду в часі.

A study of the process of activation of molybdenumboride catalyst in the reaction of epoxidation of octene-1 with tert-butyl hydroperoxide and the effect on this process of the initial concentration of octene-1, tert-butyl hydroperoxide and the amount of catalyst in the reaction mixture. As well as reaction products (tert-butyl alcohol and epoxy). It is shown that over time a new amorphous phase is formed on the surface of Mo2B, which actually catalyzes the epoxidation reaction of octene-1 with tert-butyl hydroperoxide. The formation of this phase is the reason for the acceleration of the rate of consumption of hydroperoxide and the selectivity of the formation of epoxide over time.
Вплив умов реакції гідропероксидного епоксидування октену-1 на процес активування Mo2B і на селективність утворення епоксиду
Keywords: окиснення; кінетичні закономірності; каталізатор; олефін; oxidation; kinetic laws; catalyst; olefin